Lake and Stream Buffer Zone Widths' Effects on Nutrient Export to Lake Rawapening, Central Java, Indonesia: A Simple Simulation Study - F. Maftukhakh Hilmya Nada; Nunung Puji Nugroho; Nurzawani Binti Md Sofwa (Universitas Muhammadiyah Surakarta, 2023)
Lake ecosystems in Indonesia face serious environmental problems. One of those problems is eutrophication caused by excessive plant nutrients, particularly nitrogen (N) and phosphorus (P). Water quality degradation and biodiversity loss are the effects of eutrophication. The government of Indonesia (GoI) has issued a regulation on determining lake and stream buffer zones, but it has not been fully implemented in the field. Additionally, the data related to the effects of each buffer zone width is not available. This study aims to begin to fill this gap. It simulates the effect of lake and stream buffer zone widths on nutrient export to Rawapening Lake. The Nutrient Retention sub-model, which is part of InVEST (Integrated Valuation of Environmental Services and Tradeoffs) software, has been used for this research to analyse information from several data sources, including a Digital Elevation Model (DEM) and measurements of soil depth, annual rainfall, land cover/use, watershed/sub-watershed boundaries, and biophysical conditions. Several studies of eutrophication in Rawapening Lake have measured the magnitude of eutrophication but have not discussed the effects of buffer zone widths. Therefore, this study accommodates the updated data on how much effect of buffer zone widths on the reduction of nutrient export. Five scenarios of buffer zone width are considered: 30 m., 90 m., and 150 m, where the lake buffer zone widths and the stream buffer zone width are 30 m. The results indicated that the maximum nutrient export reduction of lake buffer zones was only 2.63% (for N) and 3.56% (for P). On the other hand, the 30 m stream buffer zone width reduced the nutrient export to Rawapening Lake by up to 43.05% for N and by 44.90% for P. A 30 m combined lake and stream buffer zone width slightly increases the nutrient export reduction effectiveness, i.e., 0.41% and 0.56% for N and P, respectively.